2022
DOI: 10.1038/s41522-022-00289-w
|View full text |Cite
|
Sign up to set email alerts
|

Early microbial markers of periodontal and cardiometabolic diseases in ORIGINS

Abstract: Periodontitis affects up to 50% of individuals worldwide, and 8.5% are diagnosed with diabetes. The high-comorbidity rate of these diseases may suggest, at least in part, a shared etiology and pathophysiology. Changes in oral microbial communities have been documented in the context of severe periodontitis and diabetes, both independently and together. However, much less is known about the early oral microbial markers of these diseases. We used a subset of the ORIGINS project dataset, which collected detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In general, in this study, a negative correlation of Prevotella with genera such as Streptococcus, Neisseria and Capnocytophaga was determined. This finding are in line with the analysis of periodontitis patients, where there is a negative correlation of pathobionts in relation to genera associated with oral health, such as Capnocythophaga, Rothia, Veillonella, Streptococcus, Haemophilus, Corynebacterium, Leptotrichia and Actinomyces (Cai et al, 2021;Ai et al, 2017;Chen et al, 2018;Marotz et al, 2022). In addition, in a previous study focused on patients who received periodontal dental treatment, the authors observed a decrease in pathogenic genera such as Porphyromonas, Tanerella, Prevotella and Filifactor, as well as an increase of previously mentioned species associated with health, sustaining that the microbiota is significantly associated with the development of periodontal disease and that this can be modified with dental procedures (Chen et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…In general, in this study, a negative correlation of Prevotella with genera such as Streptococcus, Neisseria and Capnocytophaga was determined. This finding are in line with the analysis of periodontitis patients, where there is a negative correlation of pathobionts in relation to genera associated with oral health, such as Capnocythophaga, Rothia, Veillonella, Streptococcus, Haemophilus, Corynebacterium, Leptotrichia and Actinomyces (Cai et al, 2021;Ai et al, 2017;Chen et al, 2018;Marotz et al, 2022). In addition, in a previous study focused on patients who received periodontal dental treatment, the authors observed a decrease in pathogenic genera such as Porphyromonas, Tanerella, Prevotella and Filifactor, as well as an increase of previously mentioned species associated with health, sustaining that the microbiota is significantly associated with the development of periodontal disease and that this can be modified with dental procedures (Chen et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The results of Marotz et al. confirmed that the log ratio of Treponema and Corynebacterium is a novel microbial indicator of periodontitis, and the increase in the detection rate of Treponema predicts the trend of periodontitis ( Marotz et al., 2022 ). Diabetes has been reported to significantly increase the expression levels of these genera in the oral cavity ( Sabharwal et al., 2019 ; Sun et al., 2020 ; Balmasova et al., 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that the Spirochaetota flora accounts for 50% of the subgingival microbial population in periodontitis and less than 1% in healthy individuals (Chan and McLaughlin, 2000). They were found to be significantly higher in relative abundance in moderate-to-severe periodontitis (Listgarten and Levin, 1981;Armitage et al, 1982) the log ratio of Treponema and Corynebacterium is a novel microbial indicator of periodontitis, and the increase in the detection rate of Treponema predicts the trend of periodontitis (Marotz et al, 2022). Diabetes has been reported to significantly increase the expression levels of these genera in the oral cavity (Sabharwal et al, 2019;Sun et al, 2020;Balmasova et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although firm conclusions were not drawn due to different limitations in study design, several systematic reviews have reported that periodontitis might be associated with nosocomial/aspiration pneumonia [ 34 , 35 ], in particular in patients admitted in intensive care units (ICU) and those admitted for a long period (OR 2.55) [ 36 ]. Very interestingly, a study on 787 healthy patients (whose data were recollected from the ORIGINS project database) revealed that the log-ratio of Treponema to Corynebacterium bacteria might be a novel microbial indicator of periodontitis (MIP) that correlates with poor periodontal health and cardiometabolic markers early in disease pathogenesis in both the subgingival plaque and saliva [ 37 ].…”
Section: Periodontitis and Chronic Non-communicable Diseasesmentioning
confidence: 99%